Modern vertical deformation above the Sumatran subduction zone : paleogeodetic insights from coral microatolls - Zachariasen, Judith (2013)
Coral microatolls from the coast and outer-arc islands of Western Sumatra retain a stratigraphic and morphologic record of relative sea-level change, which is due in large part to vertical tectonic deformation above the Sumatran subduction zone. Low water levels, whose fluctuations produce measurable changes in coral morphology, limit the upward growth of the microatolls. Annual rings, derived from seasonal variations in coral density, serve as an internal chronometer of coral growth. The microatolls act as natural long-term tide gauges, recording sea-level variations on time scales of decades. Field observations and stratigraphic analysis of seven microatolls, five from the outer-arc islands and two from the mainland coast, indicate that the Mentawai Islands have been submerging at rates of 4–10 mm/yr over the last four or five decades, while the mainland has remained relatively stable. The presence of fossil microatolls up to several thousand years old in the intertidal zone indicates that little permanent vertical deformation has occurred over that time. Thus, most of the strain accumulated in the past few decades represents interseismic deformation that is recovered during earthquakes. Elastic dislocation models using these submergence data suggest that elastic strain is being accumulated in the interseismic period and that the subduction zone in this region is fully coupled.